Aktivity pražských křesťanských církví ve veřejném (post)sekularizovaném prostoru - Klingorová, Kamila (Lidé města, 2020)
With the growing secularization of society, the privatization of religion, and low trust in religious institutions, Prague Christian churches are having a hard time in succeeding. Nevertheless, most of them can find their place in society, providing activities beyond worship for their adherents and the general public. This contribution focuses on the social and cultural activities of Christian churches in Prague, analyzing the factors influencing the role of churches in the socio-cultural life of city communities and the openness of their activities for the general, nonbelieving public. This contribution builds on data collected about the location and activities of all Prague church institutions and on interviews with representatives of the 14 biggest Christian churches. The analysis identifies and further discusses the influence of the size and character of the parish community, its location, the means of communicating with the public, and the premises of the facilities on the scope and focus of socio-cultural activities. The scope and focus of church socio-cultural activities differ from one parish to another based on the identified factors; however, most of the parish communities focus on those activities that are needed in the given location. This contribution concludes stating that the spiritual, community, and secular dimensions blend in the activities that the parishes provide. The space they create for their adherents and the public has the character of a shared public space, whereby the Christian dimension remains present in the background, especially in the motivations and ethical principles.